2010
DOI: 10.1007/s10964-010-9565-y
|View full text |Cite
|
Sign up to set email alerts
|

When Biased Language Use is Associated With Bullying and Dominance Behavior: The Moderating Effect of Prejudice

Abstract: Biased language related to sexual orientation is used frequently among students and is related to prominent social concerns such as bullying. Prejudice toward gay, lesbian, bisexual, and transgender individuals also has been examined among adolescents, but separately from these behaviors. This study tested whether biased language use was associated with bullying and dominance irrespective of sexual prejudice or if sexual prejudice moderated these associations among 290 high school students (50% female; 56% Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
73
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 27 publications
7
73
0
5
Order By: Relevance
“…No que tange à variável "contato com homossexuais", os participantes do gênero masculino são frequentemente identificados como mais preconceituosos e menos propensos à amizade com um estudante de minoria sexual (Poteat & DiGiovanni, 2010;Poteat, Espelage, & Koenig, 2009). Contudo, segundo Cerqueira-Santos e cols.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…No que tange à variável "contato com homossexuais", os participantes do gênero masculino são frequentemente identificados como mais preconceituosos e menos propensos à amizade com um estudante de minoria sexual (Poteat & DiGiovanni, 2010;Poteat, Espelage, & Koenig, 2009). Contudo, segundo Cerqueira-Santos e cols.…”
Section: Discussionunclassified
“…Contudo, a homofobia, percebida hoje como um fenômeno recorrente no contexto escolar (Mahan e cols., 2006), ainda é pouco associada com bullying nos estudos científicos nacionais, muito embora, assim como nos resultados deste artigo, Poteat (2008) já havia sinalizado que jovens autores de bullying também apresentam altos níveis de atitudes negativas contra a juventude LGBT, além de uma maior utilização de termos homofóbicos. Esses alunos mais preconceituosos tendem a usar mais conteúdos homofóbi-cos ao praticar o bullying, se comparados a outros autores que exibemmenor preconceito (Poteat, & DiGiovanni, 2010).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A previous study demonstrated similar differences in the association between the use of discriminatory language regarding sexual orientation and bullying in schools. Male students tended to use sexually discriminatory language 21 (17,24) 23 (20,26) 22 (20,24) 12 (10,15) 11 (9,13) 13 (12,15) 8 (4, 11) 10 (7, 12) 8 (7, 9)…”
Section: Discussionmentioning
confidence: 99%
“…In a similar manner, earlier investigations have shown that homophobic behavior is correlated with sexual prejudice, wherein individuals who express stronger negative attitudes toward lesbian and gay individuals are more likely to use homophobic epithets and engage in more homophobic aggression (Poteat & DiGiovanni, 2010). We draw from the social psychological literature on social identity theory (Tajfel & Turner, 1986) to frame the connection between sexual prejudice and homophobic behavior.…”
Section: Contextual Effects Of Peer Attitudes and Behaviorsmentioning
confidence: 96%